AB0599 Interleukin-35 in Idiopathic Inflammatory Myopathies. (15th July 2016) - Mann, H.; Krystufkova, O.; Hulejova, H.; Zamecnik, J.; Hacek, J.; Filkova, M.; Vencovsky, J.; Senolt, L.
Abstract : Background: Interleukin-35 (IL-35) is a newly described heterodimeric cytokine that belongs to the IL-12 family and consists of p35 (IL-12a) and EBI3 (IL-27b) subunits. IL-35 exerts immunomodulatory activities in several autoimmune inflammatory diseases. Objectives: The aim of this study was to assess IL-35 expression in muscle tissue of patients with idiopathic inflammatory myopathies (IIM) and to compare serum levels of IL-35 in patients with IIM to healthy controls and asses potential association with activity of IIM. Methods: The expression of IL-35 was studied in a series of 19 muscle biopsy samples of idiopathic inflammatory myopathies (9 dermatomyositis, 10 polymyositis) and 10 non-inflammatory control muscle biopsies from patients with myasthenia gravis.Serum levels of IL-35 were measured in 23 PM, 28 DM and 15 cancer associated myositis patients as well as in 40 healthy controls.Disease activity was evaluated by the Myositis Disease Activity Assessment Tool (MYOACT) and by serum muscle enzymes. Results: Both IL-35 subunits were found in immune cells of the inflammatory infiltrates in IIM muscle biopsies, no immunoreactivity was observed in muscle tissue of control patients.IL-35 serum levels were increased in all IIM patients compared to healthy controls (p<0.001). There were no differences in IL-35 serum levels between myositis subgroups. Serum IL-35 levels correlated with the overall MYOACT score, with extramuscular and muscle domains of MYOACT, with physician's global activity assessment and lactate dehydrogenase levels. Conclusions: IL-35 subunits are overexpressed in inflammatory infiltrates in muscle tissue of IIM patients and elevated circulating IL-35 levels correlate with several disease activity parameters. These data suggest potential role of IL-35 in the pathogenesis of inflammatory myopathies. Acknowledgement: Supported by MHCR support for conceptual development of a research organization (023728) and BTCure (115142–2). Disclosure of Interest: None declared